2016
DOI: 10.1094/cchem-05-15-0107-r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Starch Particles for Use in Pickering Emulsions

Abstract: Cereal Chem. 93(2):116-124Particle-stabilized emulsions, called Pickering emulsions, can be produced by using starch particles. In this work we studied how the properties of the starch particles affect the droplet size and creaming of such emulsions. In the study, various sizes of starch particles were generated by two different methods and used to stabilize Pickering emulsions. Sedimentation according to Stokes' law was used to separate small and large starch granules. Acid hydrolysis was another method used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 32 publications
4
39
0
4
Order By: Relevance
“…It was shown by Saari et al [225] that small starch particles obtained by starch granules hydrolysis stabilized smaller droplets than the original granules. However, surprisingly, the resulting Pickering emulsion droplet sizes, in the studies presented in Table 2, [187] and Marto et al [226].…”
Section: Promising Pickering Emulsions For Pharmaceutical Applicationsmentioning
confidence: 95%
“…It was shown by Saari et al [225] that small starch particles obtained by starch granules hydrolysis stabilized smaller droplets than the original granules. However, surprisingly, the resulting Pickering emulsion droplet sizes, in the studies presented in Table 2, [187] and Marto et al [226].…”
Section: Promising Pickering Emulsions For Pharmaceutical Applicationsmentioning
confidence: 95%
“…Starch granules potentially contribute to the stability of the air-water interface of sponge cake batter (Lam, Velikov, & Velev, 2014;Saari, Heravifar, Rayner, Wahlgren, & Sjöö, 2016). Said stabilization of interfaces by particles is referred to as Pickering stabilization (Li, Li, Sun, & Yang, 2013;Ramsden & Gotch, 1903).…”
Section: Wheat Flourmentioning
confidence: 99%
“…Karaman et al reported that the creep compliance ( J c ) values of ketchup increased with increasing temperature within the whole concentration range, indicating that higher temperature promoted deformation in the ketchup. As reported by Saari et al and Zhu et al , the modification has little effect on the internal structure of starch granules, and the gelatinization temperature of the modified starch is between 65 and 77 °C. Therefore, we speculated that the phenomena of elasticity and viscosity increasing with temperature were caused by macromolecular entanglement and amylose dissolution during gelatinization, respectively .…”
Section: Resultsmentioning
confidence: 62%